Invasive round goby Neogobius melanostomus has sex-dependent locomotor activity and is under-represented in catches from passive fishing gear compared with seine catches - Žák, Jakub; Jůza, Tomáš; Blabolil, Petr; Baran, Roman; Bartoň, Daniel; Draštík, Vladislav; Frouzová, Jaroslava; Holubová, Michaela; Ketelaars, Henk A M; Kočvara, Luboš; Kubečka, Jan; Mrkvička, Tomáš; et al. (Journal of fish biology, 2018)
The higher proportion of males of the invasive round goby Neogobius melanostomus in samples from two activity selective passive fishing gears compared with one activity non-selective fishing gear in three Dutch lakes is related to higher male locomotory activity and is a sex-dependent trait. This difference in activity reflects the different ecology of male and female N. melanostomus.
Keywords: Animals; Male; ženské pohlaví; jezera; lokomoce; Introduced Species; zavlečené druhy; fenotyp; Lakes; zvířata; Ecology; mužské pohlaví; Phenotype; ekologie; Female; Perciformes; Locomotion